The relationship between ostracism and negative risk-taking behavior: the role of ego depletion and physical exercise - Chen, Fang; Wang, Jinhong; Gao, Heng; Zeng, Yadi; Li, Ziwei; Zou, Hongyu (Frontiers in Psychology, 2024)
Background: As a major public health problem globally, negative risk-taking behavior of college students may be related to their ostracism experience, but the reason for this association is unclear. Based on the limited resource theory, combined with the integrative model of athletic performance, we tested a moderated mediation model in which ego depletion mediated the association between ostracism and risk-taking, and physical exercise moderated the mediation process to examine the mechanisms underlying the association between ostracism and negative risk-taking behavior. Methods: 1,307 students (43% female) from four universities in China were recruited using cluster random sampling. The experience of being ostracized, ego depletion, physical exercise level, and negative risk-taking behavior were measured through an anonymous online questionnaire in “www.Sojump.com”. Results: After controlling for gender and grade in college, ostracism was positively related to negative risk-taking behavior; ego depletion mediated this relationship; and physical exercise level attenuated these direct and indirect relationships. Conculsion: The results highlight individual risk and protective factors associated with negative risk-taking behavior, and provide new perspectives on ways to prevent and reduce college students’ negative risk-taking behavior.